CONTENTS OF PLANT PIGMENTS IN MEDICINAL PLANTS OF FAMILY LAMIACEAE IN W. BALKANS AS AN INDICATOR OF POTENTIAL ANTIOXIDANT ACTIVITY - Redzic, S.; Sejdic, N.; Pilipovic, S.; Palic, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plant pigments (chlorophyll and carotenoids) are a very important group of primary metabolites. Besides their role in the process of photosynthesis and plant protection from extensive radiation, they have appliancation in pharmaceutical industry, cosmetology and dietetic. Plant pigments are also play significant role in anti-oxidant activity. The aim of this study was the qualitative/quantitative analysis of primary and secondary pigments in selected medicinal species of wild flora in BiH, including endemic species. Plant material was collected during different seasons. It was transported fresh to laboratories where qualitative (paper and thin layer chromatography) and quantitative (specterphotometric) analysis was carried out. Results showed significant presence of chlorophyll a, chlorophyll b and carotenoides. Ratio between chlorophyll a and chlorophyll b is rarely 3:1, as stated in classical literature but rather close to 3:2 and more, which makes these species even more medical and gives them higher potential anti-oxidant capacity.